Effective and Efficient Compromise Recovery for Weakly Consistent Replication - Kotla, Ramakrishna; Marshall, Catherine C.; Ramasubramanian, Rama; Rodeheffer, Tom; Terry, Doug; Wobber, Ted (EuroSys 2009: Proceedings of the 4th ACM European Conference on Computer systems, 2009)
Weakly consistent replication of data has become increasingly important both for loosely-coupled collections of personal devices and for large-scale infrastructure services. Unfortunately, automatic replication mechanisms are agnostic about the quality of the data they replicate. Inappropriate updates, whether malicious or simply the result of misuse, propagate automatically and quickly. The consequences may not be noticed until days later, when the corrupted data has been fully replicated, thereby deleting or overwriting all traces of the valid data. In this sort of situation, it can be hard or impossible to restore an entire distributed system to a clean state without losing data and disrupting users. Polygraph is a software layer that extends the functionality of weakly consistent replication systems to support compromise recovery. Its goal is to undo the direct and indirect effects of updates due to a source known after the fact to have been compromised. In restoring a clean replicated state, Polygraph expunges all data due to a compromise or derived from such data, retains as much uncompromised data as possible, and revives valid versions of subsequently compromised data. Our evaluation demonstrates that Polygraph is both effective, retaining uncompromised data, and efficient, re-replicating data only when necessary.